A follow-up study on the novel use of contrast-enhanced susceptibility-weighted imaging for extremity desmoid fibromatosis response assessment - Raul F. Valenzuela; Elvis Duran-Sierra; Mathew Antony; Behrang Amini; Sam Lo; Keila. E. Torres; Ken-Pin Hwang; Jingfei Ma; R. Jasson Stafford; Ravin Ratan; John E. Madewell; Dejka Araujo; et al. (Scientific Reports)
Abstract Desmoid tumors are rare mesenchymal neoplasms characterized by a clonal proliferation of fibroblasts and myofibroblasts. Using the novel contrast-enhanced susceptibility-weighted imaging (CE-SWI) for characterizing desmoid tumors can enhance the separation between fibrous T2-hypointense and cellular T1-enhancing components. We aim to evaluate the effectiveness of the CE-SWI signal, volumetric, and radiomics-derived features in assessing desmoid treatment response. This IRB-approved study included 17 single-lesion extremity desmoid fibromatosis patients who underwent standard-of-care MRI, including CE-SWI, from March 2021 to February 2024. Measurements of maximum diameter, volume, and the modified Choi (m-Choi: tumor/muscle T2 ratio) were computed based on CE-SWI and T2-STIR volumetric tumor segmentations. 107 shape, first-order, and textural radiomic features were calculated. Patient response was assessed using conventional RECIST as a reference standard and compared against T2-STIR and CE-SWI volumetric, m-Choi, and radiomics features. RECIST-progression (n = 3): In two patients, CE-SWI volume detected progression 10 months earlier than T2-STIR-based RECIST. Only 33% were characterized as progression by the routine radiologic report (RRR). RECIST-stability (n = 14): 5% exhibited at least one expected first-order response/progression-related change in the mean, skewness, 10th percentile, or 90th percentile, with all four changes present in 33% of cases. In RECIST-progression, CE-SWI showed an average of 15% more voxels at the 90th percentile than T2-STIR. Volume and CE-SWI/T2-STIR shape-derived size dimensional features demonstrated the highest separation between progressive and responding patients. CE-SWI has a higher sensitivity than T2-WI in detecting the active/progressive enhancing component. Volume and Shape-derived and, to a lesser extent, textural radiomic features and m-Choi effectively distinguish between progressive and responding cases, outperforming first-order radiomics, RRR, and RECIST. Particularly, progression prediction by CE-SWI/T2-STIR-volume and response prediction by CE-SWI-m-Choi outperform and precede RRR and RECIST. The novel CE-SWI enhances tumor insight and desmoid treatment-response prediction by effectively separating responding T2-hypointense-collagenized-mature components from potentially progressive T1-shortened/enhancing T2-hyperintense-immature components.